Forty years and still growing: Journal of Archaeological Science looks to the future. (April 2015) - Torrence, Robin; Martinón-Torres, Marcos; Rehren, Th.
Abstract: This special issue honours Richard Klein's outstanding contributions to archaeology through his seminal role as a senior editor for the Journal of Archaeological Science ( JAS ). The papers presented here assess achievements in archaeological science during the 40 years of research since JAS began, and scope the future within evolutionary and social theory in archaeology and across the fields of dating, aDNA, environmental reconstruction, diet, subsistence, artefact technology and function, and provenancing. Science is shown to be integral to archaeology as a whole, but challenges are identified particularly in the continuing search for new methods to answer key questions and the maintenance of rigour, significance, sustainability and social responsibility. Highlights: Papers honour Richard Klein's editorial contributions to archaeological science. Archaeological science integrates theory and method to study the human past. Advances across archaeological science are critically reviewed. Future challenges include rigour, significance, sustainability and social responsibility.